2015
DOI: 10.1128/mbio.00593-15
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pathogenic Mammalian Orthoreovirus from Diarrheic Pigs and Swine Blood Meal in the United States

Abstract: Since May 2013, outbreaks of porcine epidemic diarrhea have devastated the U.S. swine industry, causing immense economic losses. Two different swine enteric coronaviruses (porcine epidemic diarrhea virus and Delta coronavirus) have been isolated from the affected swine population. The disease has been reported from at least 32 states of the United States and other countries, including Mexico, Peru, Dominican Republic, Canada, Columbia, Ecuador, and Ukraine, with repeated outbreaks in previously infected herds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 40 publications
4
64
0
Order By: Relevance
“…Within each litter, one piglet was identified for longitudinal follow-up during the entire suckling period. A dry cotton rectal swab (Copan) was collected from each individual piglet at days 1,5,8,11,14,17,20 and 22 after birth. The swab was placed immediately in 2 ml of viral transport medium (phosphate buffered saline containing 1000 U/ml penicillin (Continental Pharma, Puurs, Belgium), 1 mg/ml streptomycin (Certa, Braine l′Alleud, Belgium), 1 mg/ml gentamicin (Life Technologies) and 0.01% v/v Fungizone (Bristol-Myers Squibb, Braine l′Alleud, Belgium)) in a sterile 15 ml falcon tube (Sarstedt) and stored at −20 °C.…”
Section: Sanger Sequencing Of Porcine Kobuvirus Polymerase Gene a Pomentioning
confidence: 99%
“…Within each litter, one piglet was identified for longitudinal follow-up during the entire suckling period. A dry cotton rectal swab (Copan) was collected from each individual piglet at days 1,5,8,11,14,17,20 and 22 after birth. The swab was placed immediately in 2 ml of viral transport medium (phosphate buffered saline containing 1000 U/ml penicillin (Continental Pharma, Puurs, Belgium), 1 mg/ml streptomycin (Certa, Braine l′Alleud, Belgium), 1 mg/ml gentamicin (Life Technologies) and 0.01% v/v Fungizone (Bristol-Myers Squibb, Braine l′Alleud, Belgium)) in a sterile 15 ml falcon tube (Sarstedt) and stored at −20 °C.…”
Section: Sanger Sequencing Of Porcine Kobuvirus Polymerase Gene a Pomentioning
confidence: 99%
“…KU558701) at 1 × 10 5 plaque-forming unit (PFU)/ml (4 ml per pig) and MRV-ZJ2013 at 6 × 10 6 PFU/ml (4 ml per pig), respectively. The challenge dosage of MRV-ZJ2013 in group C referred to a recent study (Thimmasandra Narayanappa et al, 2015). All pigs were monitored daily for rectal temperature and clinical signs.…”
Section: Pathogenesis Study In Neonatal Pigsmentioning
confidence: 99%
“…However, in the last decade, increasing numbers of studies in humans and other mammals have shown that they can cause severe illness in humans and other mammals, including upper respiratory tract infections, encephalitis, and diarrhea (Chua et al, 2008;Ouattara et al, 2011a;Steyer et al, 2013a). MRVs have been isolated from a broad range of mammalian species, including bats (Hu et al, 2014;Kohl et al, 2012;Lelli et al, 2013;Lorusso et al, 2014;Thalmann et al, 2010;Wang et al, 2015a;Yang et al, 2015), civet cats , cows (Anbalagan et al, 2014), mink (Lian et al, 2013), pigs (Dai et al, 2012b;Kwon et al, 2012b;Thimmasandra Narayanappa et al, 2015;Zhang et al, 2011a), dogs (Decaro et al, 2005) and humans (Chua et al, 2008;Ouattara et al, 2011b). However, porcine MRV failed to arouse the concern of researchers until 2007, when it was first reported as the cause of diarrhea in newborn piglets in China (Zhang et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel MRVs have recently been identified in several hosts, including bats in Italy and Germany [ 16 , 17 ], and a novel Orthoreovirus , with a high similarity to the MRVs found in bats in Europe, was detected in Slovenia from a child requiring hospitalization due to acute gastroenteritis [ 15 ]. Recently, a virulent MRV containing an S1 segment that was strongly homologous to bat MRV3 was detected from diarrheic pigs in the United States [ 18 ]. In addition, a bat-borne fusogenic Orthoreovirus with zoonotic potential was detected from healthy flying foxes ( Pteropus vampyrus ) legally imported from Indonesia to Europe [ 19 ].…”
Section: Introductionmentioning
confidence: 99%